Konstruksi Safe Space Di Media Sosial (Analisis Wacana Digital Tentang Safe Space di Komunitas Ohmybeautybank Pada Media Sosial X) - Kurnia Nur Khasanah; Syafrida Nurrachmi Febriyanti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study examines how the discourse of safe space is constructed by the women's community OhMyBeautyBank on the social media platform X. Utilizing Rodney H. Jones’ digital discourse analysis approach, the research explores aspects of text, context, interaction, as well as ideology and power. The study highlights the community’s reactions to external threats in the form of digital sexual harassment, which emerged following a call from external accounts to “scout” female users within the community. Findings reveal that the community constructs a safe space through emotional expression, member solidarity, labeling outsiders as predators, and calls for mutual protection. This study concludes that the OhMyBeautyBank digital community functions not only as a space for sharing but also as a site of resistance against patriarchal power within the open ecosystem of social media. Through solidarity and strategic language use, they create an alternative safe space capable of responding to gender-based threats in a collective and reflective.